Crystal structure of the PX domain of Vps17p from Saccharomyces cerevisiae. Issue 5 (4th May 2022) - Obita, Takayuki; Inaka, Koji; Kohda, Daisuke; Maita, Nobuo
Abstract : The crystal structure of the PX (phox homology) domain of the Saccharomyces cerevisiae Vps17p protein was determined. The absence of basic residues around the canonical binding site suggests an inability to bind phosphatidylinositol phosphate molecules. Abstract : The structure determination of the PX (phox homology) domain of the Saccharomyces cerevisiae Vps17p protein presented a challenging case for molecular replacement because it has noncrystallographic symmetry close to a crystallographic axis. The combination of diffraction‐quality crystals grown under microgravity on the International Space Station and a highly accurate template structure predicted by AlphaFold 2 provided the key to successful crystal structure determination. Although the structure of the Vps17p PX domain is seen in many PX domains, no basic residues are found around the canonical phosphatidylinositol phosphate (PtdIns‐P) binding site, suggesting an inability to bind PtdIns‐P molecules.